Web development with Angular 2 and Bootstrap - Sharma, Tarun; Clark, Tory; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"This course demonstrates how to write dynamic, feature-rich Angular 2 applications with Bootstrap's responsive layouts and end-to-end testing techniques. We will set up our development environment with Angular 2 and ES6 with TypeScript. In Angular 2, everything is a component using TypeScript annotations. This course takes a component-centric approach, using them as the main point of discussion to help you learn the core concepts in Angular 2. You'll also get to grips with Bootstrap to create and design web applications that are elegantly styled with a responsive user interface."--Resource description page.
Title from resource description page (Safari, viewed February 16, 2017).
Presenter, Tory Clark.
Keywords: Bootstrap (Computer program); AngularJS (Software framework); Web site development; Web sites -- Design; Electronic books